Jurassic World [videorecording (DVD)] - Trevorrow, Colin, 1976-; Pratt, Chris, 1979-; Howard, Bryce Dallas, 1981-; Simpkins, Ty; Khan, Irrfan, 1967-2020-; D'Onofrio, Vincent (Universal Studios Home Entertainment, 2015)
Twenty-two years following the events of Jurassic Park, Isla Nublar now includes a completely functioning dinosaur theme park, as once envisioned by John Hammond. After ten years of operation and decline in visitors, a unique attraction is designed to ignite visitor's interest, which fails horribly.